(untitled) (Research, Society and Development, 2021)
Introduction: Current paradigms in health anthropology seek to emphasize aspects such as interaction and relationality inherent to social practices in health, through care. Chronic Non-Communicable Diseases (NCDs) are the leading causes of death and disability worldwide. This essay seeks to present a reflection on the contributions of the anthropology of health and disease to the construction of new health practices. Methodology: This essay was produced from debates and bibliographic references worked in the classroom during the course of Social Science Seminars, of the Graduate Program in Public Health, at the Federal University of Santa Catarina (UFSC). Final considerations: The global increase in incidence raises awareness of health and the care provided in Primary Health Care (PHC) to these diseases. The focus given within care is based on preventive strategies based on changing the behavior of individuals, which often fails due to the lack of adherence to the therapeutic issue.